Table of Content - -, (Journal of Islamic Sciences, 2023)
Table of Content1. Examples of jurisprudential rules and their applications in the judgments of social mediaMrs. Nadira Tariq Al-Omar2. The Modern Interpretation of the Prophet's Sunnah (Purposes and Risks)Dr. Hamzah Faiei Ibraheem Alfathi3. Christian-Islamic dialogue and Orientalism problemMrs. Nora Mohammed Al-Ajmi4. The sent interests at Al-Hanafiyya and their contemporary applications in personal statusMr. Rakan Khalaf Mahasneh Almwadih5. Timeline for An-Nisa’ based on occasions of revelationMr. Rashid Issack Ali6. Treasure is a creature, not a creatorProf. Ibtissam Ibrahim Baydoun7. Substantive defenses in the cases of the donor in the donation lawsuitsMrs. Razan Yousef Al-Wazzan, Co-Prof. Asim Abdullah Al-Mutawa
Keywords: Journal of Islamic Sciences